Genes in common diseases - Lou, Jennie (Henry Stewart Talks, 2007)
Nature vs. nurture, Types of genetic disorders, Continuum of genetic influence, Breast cancer: epidemiology, clinical manifestation and genetic factors, Genetic testing and future research in breast cancer, Colorectal cancer: epidemiology, genetic factors, risk factors and clinical manifestation, Screening and diagnosis of colorectal cancer, APC gene, Genetic testing, FAP testing, Database and resources
Reviewed at 2018/02/08